2021
DOI: 10.5209/ltdl.76464
|View full text |Cite
|
Sign up to set email alerts
|

Misgendering as epistemic injustice: A queer STS approach

Abstract: Misgendering is perceived as the use of incorrect pronouns and gender categories when addressing Transgender and Gender Non-Conforming (TGNC) people. This common habit is widely observed in reports, surveys and assessments, where the pressures to comply with a binary understanding of gender are high and alternative options for self-identification are not frequently offered. The present study reads misgendering as a manifestation of epistemic injustice, and uses resources from Science, Technology and Society (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This paper builds on previous arguments about the relevance of epistemic injustice to misgendering (Argyriou, 2021), and situates this work in an empirical case. This paper also builds upon work done to understand the safety concerns of women in online knowledge sharing platforms (Menking et al, 2019), and extends this work to diverse gender identities.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This paper builds on previous arguments about the relevance of epistemic injustice to misgendering (Argyriou, 2021), and situates this work in an empirical case. This paper also builds upon work done to understand the safety concerns of women in online knowledge sharing platforms (Menking et al, 2019), and extends this work to diverse gender identities.…”
Section: Introductionmentioning
confidence: 82%
“…Misgendering -or referring to someone in a way that does not respect their gender identity -is a common form of harassment that trans and nonbinary people experience online and offline. Misgendering is experienced chiefly through language and testimony, and can often be a result of linguistic conventions at a structural level (Argyriou, 2021). Being misgendered causes trans and nonbinary people to feel stigma, and previous research has suggested that this stigma is experienced most frequently by people who identify as genderqueer (McLemore, 2015).…”
Section: Trans and Nonbinary Experiences Onlinementioning
confidence: 99%